DETERMINATION OF COMPETENCE, TRAINING AND CULTURE OF THE ORGANIZATION WITH THE MOTIVATION OF WORKING AS A VARIABLE OF THE MEDIATOR ON THE PERFORMANCE OF HEALTH TRAINING HALL OFFICERS MINISTRY OF HEALTH BATAM - Herawati Herawati (Universitas Batam, 2020)
In this study, researchers used data respondents, such as gender, age and long working respondents to provide information on the characteristics of respondents. The questionnaire was spread over 35. The discussion in this chapter is the result of field studies to obtain a questionnaire that measures the five main variables in the study, such as training, organizational culture, work motivation and employee performance. Analysis of data with parametric and non parametrics statistics by using SEM-PLS (structural Equation Modelling-Partial Least Square) regarding the research variables, test of instruments, test normality, hypothesis testing, as well as discussion of the hypothesis test results and path Analysis Path. This study uses path analysis to test relationship patterns that reveal the influence of variables or a set of variables against other variables, both direct influences and indirect influences. Calculation of line coefficient in this study assisted with Smart PLS Ver 3.0. To find out the direct and indirect influences between variables then be seen from the calculation result of the line coefficient and to know the significance. The effect of the X3 variable against X4 has a P-Values value of 0.010 < 0.05, so it can be stated that the effect between X3 against X4 is significant. The effect of the variable X3 against Y has a P-Values value of 0.000 < 0.05, so it can be stated that the influence between X3 to Y is significant. The effect of X4 to Y variables has a P-Values value of 0.010 < 0.05, so it can be stated that the effect between X4 to Y is significant. The effect of the X1 variable against X4 has a P-Values value of 0.014 < 0.05, so it can be stated that the effect between X1 against X4 is significant. The effect of the X1 variable against X4 has a P-Values value of 0.007 < 0.05, so it can be stated that the effect between X1 against X4 is significant. The effect of a variable X2 against X4 has a P-Values value of 0.024 < 0.05, so it can be stated that the effect of X2 against X4 is significant. The effect of a variable X2 against Y has a P-Values value of 0.047 < 0.05, so it can be stated that the effect of the X2 against Y is significant.